Virucidal Action Mechanism of Alcohol and Divalent Cations Against Human Adenovirus - Martín-González, Natalia; Vieira Gonçalves, Leonam; Condezo, Gabriela N.; San Martín, Carmen; Rubiano, María; Fallis, Ian; Rubino, Joseph R.; Ijaz, M. Khalid; Maillard, Jean-Yves; De Pablo, Pedro J. (Frontiers in Molecular Biosciences, 2020)
Hygiene and disinfection practices play an important role at preventing spread of viral infections in household, industrial and clinical settings. The development of effective virucidal formulations against non-enveloped viruses such as human adenoviruses (HAdVs), is challenging because these viruses are less susceptible to biocidal products than enveloped viruses. One approach in developing virucidal formulations is to understand the mechanisms of action of active ingredients and formulation excipients. It has been reported that zinc can increase the virucidal activity of alcohols, although the reasons for such potentiation is unclear. Here, we investigate the virucidal activity of alcohol and zinc salt combinations and their impact on HAdV using a standardized virucidal efficacy test, nucleic acid integrity assays, Atomic Force Microscopy (AFM) and Transmission Electron Microscopy (TEM). The combination of ethanol and zinc in a formulation inactivates HAdV2 upon 60 min contact time in clean conditions. No conspicuous damage to the viral genome could be observed by gel electrophoresis. However, AFM revealed drastic structural alterations of the virus particles upon treating with the ethanol-zinc combination for only a few minutes, in conditions in which no evident structural damage was observed by TEM. AFM also revealed mechanical softening of the particles induced by all formulations tested. These observations suggest that HAdV inactivation starts by subtle changes in the mechanical properties of the virion that may eventually result in its complete collapse. Viral particles must maintain a delicate regulation of stability and mechanical properties to successfully carry out their infectious cycle. Our results suggest that the combination of ethanol and zinc salts act on these properties to inactivate HAdV.